Establishment of national standard for anti-SARS-Cov-2 neutralizing antibody in China: The first National Standard calibration traceability to the WHO International Standard - Guan, Lidong; Mao, Qunying; Tan, Dejiang; Liu, Jianyang; Zhang, Xuanxuan; Li, Lu; Liu, Mingchen; Wang, Zhongfang; Cheng, Feiran; Cui, Bopei; He, Qian; Wang, Qingzhou; et al. (Frontiers in Immunology, 2023)
Neutralizing antibody (NtAb) levels are key indicators in the development and evaluation of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) vaccines. Establishing a unified and reliable WHO International Standard (IS) for NtAb is crucial for the calibration and harmonization of NtAb detection assays. National and other WHO secondary standards are key links in the transfer of IS to working standards but are often overlooked. The Chinese National Standard (NS) and WHO IS were developed by China and WHO in September and December 2020, respectively, the application of which prompted and coordinated sero-detection of vaccine and therapy globally. Currently, a second-generation Chinese NS is urgently required owing to the depletion of stocks and need for calibration to the WHO IS. The Chinese National Institutes for Food and Drug Control (NIFDC) developed two candidate NSs (samples 33 and 66–99) traced to the IS according to the WHO manual for the establishment of national secondary standards through a collaborative study of nine experienced labs. Either NS candidate can reduce the systematic error among different laboratories and the difference between the live virus neutralization (Neut) and pseudovirus neutralization (PsN) methods, ensuring the accuracy and comparability of NtAb test results among multiple labs and methods, especially for samples 66–99. At present, samples 66–99 have been approved as the second-generation NS, which is the first NS calibrated tracing to the IS with 580 (460–740) International Units (IU)/mL and 580 (520–640) IU/mL by Neut and PsN, respectively. The use of standards improves the reliability and comparability of NtAb detection, ensuring the continuity of the use of the IS unitage, which effectively promotes the development and application of SARS-CoV-2 vaccines in China.